Implications and applications of systematic reviews for evidence-based dentistry and comparative effectiveness research: A sample study on antibiotics for oro-facial cellulitis treatment - Quyen Bach; Vandan Kasar; Francesco Chiappelli (Wolters Kluwer Medknow Publications, 2015)
Introduction: Comparative effectiveness and efficacy research for analysis and practice (CEERAP) was performed to assess the effects of penicillin-based versus erythromycin-based antibiotic treatments in patients with skin and soft tissue infections (SSTIs) including cellulitis, impetigo, and erysipelas. Because SSTIs, especially orofacial cellulitis, are volatile infectious diseases of a life-threatening nature, research on the most efficacious remedies is necessary. Methods: The stringent bibliome yielded three systematic reviews, which were examined for quality of research synthesis protocol and clinical relevance. Results: The sample size of three, rendered the statistical analyses and cumulative meta-analysis problematic. Conclusion: The systematic review outlined here should aid in increasing clinical awareness, improving patient health literacy, and promoting consensus of the best evidence base (BEB) to mitigate the threat of sepsis and potential death caused by cellulitis infections.